A qualitative study of employees' loyalty working in Bank Perkreditan Rakyat in West Kalimantan - Laila Nurfitrah Lubis; Grace Kelly Hadi Putri Sihombing; Melti Oktavianda (Jurnal Mantik, 2023)
Employee loyalty is an important aspect related to the employees's loyalty, how they contribute and show their best efforts to the organization. In various conditions, improving their loyalty will ideally form engagement, where workers will devote their energy and thoughts to the maximum extent possible to achieve company goals. Employee loyalty does not appear over a short period of time and can be influenced by various factors. The researchers examine employees' loyalty to the Bank Perkreditan Rakyat Pancur Banua Khatulistiwa (BPR PANBANK). This study employs a qualitative approach with descriptive methods to provide an overview or describe various situational conditions and phenomena in social settings. This research displays employee loyalty to BPR PANBANK from three perspectives: employee loyalty to the organization, employee loyalty to leaders and employee loyalty to work